Research on The Relationship Between Executive Compensation, ESG Performance and Firm Performance Based on Mediating Effect - Chen, Jiahui (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of social economy, more and more enterprises have begun to pay attention to corporate environment, social responsibility and corporate governance (ESG), but there are still different views in the academic community on the question of whether the improvement of ESG performance can lead to the improvement of performance level, and whether the implementation of compensation incentives for executives can have an impact on the relationship between ESG performance and corporate performance. From the perspective of mediating effect, based on stakeholder theory, information asymmetry theory and reputation theory, this paper takes listed companies from 2012 to 2020 as the research object, empirically analyzes the relationship between executive compensation, corporate ESG performance and corporate performance through Multiple Regression Analysis, and further studies the mediating role of corporate ESG performance. This study not only provides a scientific basis for companies to improve their ESG performance in practice, but also provides a reference for policymakers to better balance the relationship between social responsibility and economic benefits.